A MODELAGEM MATEMÁTICA COMO METODOLOGIA DE ENSINO E APRENDIZAGEM NOS ANOS INICIAIS DO ENSINO FUNDAMENTAL - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2012)
This work presents and enables an analysis of how the Mathematical Modeling is being inserted in the scholar context, on the ambit of an investigation that seeks to answer which contributions the insertion of Mathematical Modeling, as a methodology of teaching and learning, can offer in the early years of elementary school? The delimitation of this research is predominantly of qualitative nature. The data presented was obtained using an exploratory research. The objectives of the research were: a) Contribute with the insertion of Mathematical Modeling as a methodology of teaching and learning in the ambit of the early years of elementary school; b) Point, after analytical reflections, the clarifications made by the teachers related to the perspectives of utilizing the Mathematical Modeling in the early years of elementary school. It was utilized as theoretical fundamentation the contributions from Miorim (1998) who discusses the History of the Mathematical Education, from authors who discuss the nature and methodology of the Mathematical Education (Rius, 1989a, 1989b; Kilpatrick 1996), authors who underlie the aspects and analysis of data from a qualitative research (Bogdan; Biklen, 1994; Bardin, 2011), authors who discuss the Mathematical Modeling in the ambit of the Mathematical Education (D’Ambrosio, 1999; Burak, 1992, 2010; Barbosa 2001; Meyer, 2007; Burak; Klüber, 2008, 2010), as well as authors who discuss the Education and formation of the teacher (Freire, 1981, 2005; Libâneo, 2006; Nacarato; Mengali; Passos, 2009). The research involves the analysis from teacher manifestations after concluding a formation course in service involving the Mathematical Modeling, as well as the analysis of works developed with students from the early years of elementary school, according to a Mathematical Modeling perspective. The results of the research indicate that in the ambit of early years: a) Modeling is a methodological tendency that offers contributions to the process of teaching; b) teachers explicit different perspectives of the use of Modeling.
The mathematical modeling as a methodology of teaching and learning in the early years of elementary school
Keywords: Modelagem Matemática; Educação Matemática; Anos Iniciais; Mathematical Modeling; Mathematical Education; Early years; CNPQ::CIENCIAS HUMANAS::EDUCACAO